The classroom arsenal military research, information technology, and public education - Noble, Douglas D. (Routledge revivals, 1991)
Originallly published in 1991, Douglas Noble traces the enormous, yet uncharted, influence of military research and development on post-war American public education, drawing implications for current debates about the means and ends of education in our technological society. As a case study, the book provides a detailed account of pioneering experiments in computer-based education which took place during the late 1950s within the context of military research on man-machine systems. By extracting key paradigms of this military research and demonstrating their continuity with the most recent research in computer-based education. Noble offers a new, historical perspective on the significance of computers for education. The conclusion offers a provocative analysis of the political economy underlying the recent alignment of education with technological developments in computer science, artificial intelligence and cognitive science.